The Impact of The Covid19 Pandemic on The Economy of The Border Area on The Example of The Polish-Ukrainian Borderland - Arkadiusz MALKOWSKI (Communications of International Proceedings, 2021)
The research presented in the paper aims to identify the problems affecting cross-border cooperation between Poland and Ukraine during the COVID-19 pandemic. It is based on quantitative secondary data, primary information, and an analysis of the available source literature. The research methods used include a critical analysis of the source literature, secondary data analysis, and in-depth interviews. Data made available by Statistics Poland and the Border Guard are used, along with the results of the author's own research performed in line with the CATI methodology. The results show the importance of cross-border trade for the development of the Polish-Ukrainian borderland. The present article aims to determine the problems caused by the COVID-19 pandemic and to assess their impact on the development of the border area. The problems thus identified include: reduced border traffic, decreased expenditure by foreigners in the border area, and regression of border trade. The analysis and assessment carried out in the present article shows that the COVID-19 pandemic and its consequences have affected individual areas in Poland’s eastern frontier. The closure of the border is harming the economy of that particular area. The outcome of the study can be used in developing programs for counteracting the effects of the closed border.
Keywords: cross-border area; project management; COVID-19; pandemic; eastern border of Poland.